Transcriptional regulation of Satb1 in mouse trophoblast stem cells - Yu, Wei; Chakravarthi, V. Praveen; Borosha, Shaon; Dilower, Iman; Lee, Eun Bee; Ratri, Anamika; Starks, Rebekah R.; Fields, Patrick E.; Wolfe, Michael W.; Faruque, M. Omar; Tuteja, Geetu; Rumi, M. A. Karim (Frontiers in Cell and Developmental Biology, 2022)
SATB homeobox proteins are important regulators of developmental gene expression. Among the stem cell lineages that emerge during early embryonic development, trophoblast stem (TS) cells exhibit robust SATB expression. Both SATB1 and SATB2 act to maintain the trophoblast stem-state. However, the molecular mechanisms that regulate TS-specific Satb expression are not yet known. We identified Satb1 variant 2 as the predominant transcript in trophoblasts. Histone marks, and RNA polymerase II occupancy in TS cells indicated an active state of the promoter. A novel cis-regulatory region with active histone marks was identified ~21kbp upstream of the variant 2 promoter. CRISPR/Cas9 mediated disruption of this sequence decreased Satb1 expression in TS cells and chromatin conformation capture confirmed looping of this regulatory region into the promoter. Scanning position weight matrices across the enhancer predicted two ELF5 binding sites in close proximity to SATB1 sites, which were confirmed by chromatin immunoprecipitation. Knockdown of ELF5 downregulated Satb1 expression in TS cells and overexpression of ELF5 increased the enhancer-reporter activity. Interestingly, ELF5 interacts with SATB1 in TS cells, and the enhancer activity was upregulated following SATB overexpression. Our findings indicate that trophoblast-specific Satb1 expression is regulated by long-range chromatin looping of an enhancer that interacts with ELF5 and SATB proteins.